Your Mouse Is a Database. (Communications of the ACM, 2012)
The article focuses on asynchronous data stream querying using fluent application programming interface operators provided by the Reactive Extension (Rx) library. It states that database technology corresponds to dimensions of variety, velocity, and volume and utilizes a cube diagram to graph the different database dimensions. It mentions that Rx coordinates and orchestrates event-based and asynchronous computations including short message service messages, social media status updates, and high-latency calls to Web services utilizing standard object-oriented programming languages. It talks about the creation of asynchronous data streams in the Java programming language and comments on the use of asynchronous and streaming services in web and mobile applications.